Simulating the radial dose distribution for charged particles in water medium by a semi-empirical model: An analytical approach. (December 2018) - Awad, E.M.; El Masady, I.; Rammah, Y.S.; Abu-Shady, M.
Abstract: A computational semi-empirical model based on electronic radiation damage to medium has been presented to simulate the radial dose distribution. An analytical approach was used to calculate the deposited energy in water per unit mass within a cylindrical shell of unit length around the ion path at a radial distance between r and r + dr, the so-called radial dose distribution, RDD . Detail steps were given and the final radial dose integration over the electron range between R min and R max was solved numerically using the Mid-Point Method . A validation for the present model was presented by integrating the RDD over all possible radial distances, r to yield the tabulated LET of the ion. The validation was presented for a range of proton ions of different energies. The RDD for heavy charged particles of proton, alpha, Carbon and Oxygen ions of different energies in liquid water were obtained. Good agreement between the present model and experimental, theoretical, and Monte Carlo (Geant4-DNA) data were obtained for all ions under investigations. Highlights: A semi-empirical model based on electronic radiation damage is postulated. Analytical approach code and numerical integration were used to deduce the radial dose. The radial dose for several heavy ions in liquid water was calculated. The proposed model was compared to experimental data. The model compared to many Monte Carlo codes (Geant4-DNA) simulation code.